THE INFLUENCE OF ELECTRONIC SERVICE QUALITY ON CUSTOMER SATISFACTION WITH BRAND TRUST AS A MODERATING VARIABLE - Apay Safari; Anti Riyanti; Uus Mohammad Darul Fadli (JURNAL ILMIAH EDUNOMIKA, 2024)
In line with the comprehensive explanation above, there are four actors that can influence customer satisfaction, namely product quality, price, service quality and emotionality. Of the four factors above, researchers believe that the Service Quality factor can influence Customer Satisfaction more significantly than the other three. Different from other research, what is meant by Service Quality in this research is electronic Service Quality. Apart from that, this research also added the Brand Trust variable as a moderating variable. This research is a quantitative research with a descriptive approach, namely research that has been used as a fundamental reference in previous studies to find new variations in the research being conducted, namely related to the influence of Electronic Service Quality on Employee Job Satisfaction with Brand Trus as a moderating variable. This research collected data using a questionnaire method which was distributed online to 400 Bank Bukopin employees spread throughout Indonesia. We can also say that this data is primary data. In using the SmartPLS 4.0 analysis tool and using primary data, the stages that must be passed are validity testing, reliability testing and path coefficients. This data was collected and analyzed using the smart PLS 4.0 analysis tool. The result in this article show that Electronic Service Quality can have a positive relationship and a significant influence on Consumer Satisfaction because the P-Values value is positive and is below the 0.05 significance level, namely 0.002. Apart from the first row of the second table, the third row of the third table is also the second hypothesis in this research showing that the Brand Trust variable can moderate the influence of the Electronic Service Quality variable on the Consumer Satisfaction variable because the P-Values value is positive and is below the 0.05 significance level, namely 0.000. Thus the results of the first and second hypotheses in this research can be proven and accepted. Keywords : Electronic Service Quality, Customer Satisfaction Brand Trust